The Effect of Financial Distress, Inventory Intensity and Capital Structure on Tax Aggressiveness (Food & Beverage Issuer of the Indonesia Stock Exchange Period 2019-2023) - Anissa Pujiwaty; Amor Marundha; Maidani, Maidani (Jurnal Ekonomi, 2025)
This research aims to analyze and test the influence of financial distress, inventory intensity and capital structure on tax aggressiveness. The research population is all Issuers in the Food & Beverage of the Indonesian Stock Exchange for the 2019 - 2023 Period. The variable used is Tax Aggressiveness as the dependent variable, Financial Distress, Inventory Intensity and Capital Structure as the independent variable. The sampling technique used a purposive sampling method and obtained 26 samples of issuers. The analytical methods used are Descriptive Statistical Analysis, Multiple Linear Regression Analysis and Hypothesis Testing. The results of this study show that financial distress has a negative and significant effect on tax aggressiveness, inventory intensity has a positive but not significant effect on tax aggressiveness and capital structure has a positive but not significant effect on tax aggressiveness.